2020
DOI: 10.1055/a-1112-7032
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Atenolol and Propranolol on Rat Heart Mitochondria

Abstract: Propranolol and atenolol are known as β receptor blocker drugs. These drugs are used to treat some heart diseases. There are controversies in the relationship between the use of beta-blocker drugs and the level of reactive oxygen species (ROS). Mitochondria as one of the most important sources of ROS are considered as one of the targets of drug-induced cardiotoxicity. The aim of this study was to evaluate the effects of propranolol and atenolol on mitochondria isolated from the heart. To achieve this aim, seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 39 publications
7
17
0
Order By: Relevance
“…These drugs can act at neuromuscular transmission, at both pre-and postsynaptic levels and may produce neuromuscular dysfunction. The calcium channel blockers, as verapamil and amlodipine, can impair neuromuscular transmission in individuals without neuromuscular disease, which may cause misinterpretation of single fiber electromyography studies carried out to investigate neuromuscular junction disorders (Ozkul, 2007;Seydi et al, 2020). In our study, 17% and 53% of hypertensive individuals make use calcium channel blockers and diuretics, respectively.…”
Section: Hypertension and Stomatognathic Systemmentioning
confidence: 73%
“…These drugs can act at neuromuscular transmission, at both pre-and postsynaptic levels and may produce neuromuscular dysfunction. The calcium channel blockers, as verapamil and amlodipine, can impair neuromuscular transmission in individuals without neuromuscular disease, which may cause misinterpretation of single fiber electromyography studies carried out to investigate neuromuscular junction disorders (Ozkul, 2007;Seydi et al, 2020). In our study, 17% and 53% of hypertensive individuals make use calcium channel blockers and diuretics, respectively.…”
Section: Hypertension and Stomatognathic Systemmentioning
confidence: 73%
“…Although some studies have shown antioxidant properties for Cyclosporine A and PROP independently, [ 22 , 23 ] some other studies have demonstrated their toxic effects. [ 24 ] Recent research has suggested that ROS can trigger PROP-induced cell death; therefore, ROS inhibition is responsible for reducing PROP-induced cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition can be caused by directly inhibiting the activity of MRC complexes. For example, zoniporide [ 64 ], naproxen [ 60 , 138 ], dronedarone [ 139 ], and mubritinib [ 140 ] inhibit complex I; propranolol and atenolol disrupt complex II [ 119 ]; celecoxib suppresses complex IV [ 14 ]; and As 2 O 3 inhibits complex I, III, and IV [ 141 ]. OXPHOS may also be blocked by inhibition of the expression of MRC complexes, such as by mitoxantrone [ 100 ].…”
Section: Main Properties Of Mitochondria and Drug-induced Mitochondri...mentioning
confidence: 99%
“…Drugs inducing cardiotoxicity by targeting mitochondria invariably proceed to MMP collapse and mPTP opening ( Table 3 ). Antineoplastic agents, including DOX [ 73 , 81 , 164 ], As 2 O 3 [ 84 , 229 ], and imatinib [ 91 ]; β adrenergic receptor blockers, such as propranolol and atenolol [ 119 ]; antiarrhythmic drugs dronedarone and amiodarone [ 139 ]; antibiotics erythromycin and clarithromycin; NSAIDs such as naproxen, diclofenac, and celecoxib [ 60 ]; and diabetes drug pioglitazone [ 122 ] have all been reported to cause these harmful effects. mPTP opening and MMP decrease consequently induce loss of respiratory control and imbalance in ATP production, and loss of mitochondrial components such as ATP, NAD+, and glutathione, leading to water accumulation in the matrix, which causes mitochondrial osmotic swelling, IMM unfolding, and the rupture of the OMM [ 230 , 231 ].…”
Section: Main Properties Of Mitochondria and Drug-induced Mitochondri...mentioning
confidence: 99%